2016
DOI: 10.1007/s10021-016-0084-x
|View full text |Cite
|
Sign up to set email alerts
|

Nationally Representative Plot Network Reveals Contrasting Drivers of Net Biomass Change in Secondary and Old-Growth Forests

Abstract: Uncertainty about the mechanisms driving biomass change at broad spatial scales limits our ability to predict the response of forest biomass storage to global change. Here we use a spatially representative network of 874 forest plots in New Zealand to examine whether commonly hypothesised drivers of forest biomass and biomass change (diversity, disturbance, nutrients and climate) differ between old-growth and secondary forests at a national scale. We calculate biomass stocks and net biomass change for live abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 57 publications
1
49
0
Order By: Relevance
“…National biomass estimates for a similar forest and tall shrubland association dominated by Kunzea sp. (Kunzea Wiser et al 2011) has a mean live tree aboveground biomass of 48 Mg ha −1 (6 ± 1 SE, n = 32 plots) (Holdaway et al 2017).…”
Section: Fire and Management Historymentioning
confidence: 99%
See 1 more Smart Citation
“…National biomass estimates for a similar forest and tall shrubland association dominated by Kunzea sp. (Kunzea Wiser et al 2011) has a mean live tree aboveground biomass of 48 Mg ha −1 (6 ± 1 SE, n = 32 plots) (Holdaway et al 2017).…”
Section: Fire and Management Historymentioning
confidence: 99%
“…Post-hoc tests for differences in mean cover for each group at each measurement were made using the glht function in the multcomp v.1.4-0 package (Hothorn et al 2008). Tree dimensions were converted to aboveground biomass following standard allometric methods for the species sampled (Coomes et al 2002;Holdaway et al 2014Holdaway et al , 2017. We determined the relationships between aboveground biomass and landform index using a general linear model (GLM) with Gaussian error model.…”
Section: Data Analysesmentioning
confidence: 99%
“…Aboveground live tree biomass (Mg/ha) was estimated using NZ‐specific allometric relationships and values of stem‐specific density (Holdaway et al. ). Large trees have immense cultural (Blicharska and Mikusiński ) and ecological (Lindenmayer and Laurance ) value and are defined in NZ as those with a dbh ≥ 60 cm.…”
Section: Methodsmentioning
confidence: 99%
“…A recent objective survey of NZ's indigenous forests revealed that while large trees account for only 0.8% of all stems, they contain 41% of aboveground live tree biomass (Holdaway et al. ). Evidence for tree regeneration was estimated as the frequency of woody seedlings ≥15 cm tall, by species, across 24 seedling subplots (0.75 m 2 ) spaced evenly throughout the plot (Hurst and Allen ).…”
Section: Methodsmentioning
confidence: 99%
“…In the diverse forests of eastern North America, investigating temporal and spatial distributions of biomass allocation according to species (Eisen andBarker Plotkin 2015, Dye et al 2016) and canopy position (Alexander 2017a) can add valuable information that is lost by grouping total forest carbon sequestration under a single umbrella. Investigating the structural distribution of biomass production also holds potential to add invaluable detail to our understanding of the forest carbon cycle, as forest structure and disturbance has been hypothesized to significantly impact biomass dynamics (Pan et al 2011, Gough et al 2016, Holdaway et al 2017.…”
Section: Introductionmentioning
confidence: 99%